Demirjian's system for estimating dental age among Northwestern Turkish children aged 4-16 years - (:unkn) unknown (ARIESDUE SRL, 2013)
Aim The aim of this study was to investigate the timing of individual tooth formation stages in a group of northwestern Turkish children and to evaluate the suitability of Demirjian's method. Materials and methods Study design: dental ages (DAs) were assessed from 1,678 digital panoramic radiographs of healthy children (aged 4-16 years; 743 females and 935 males). Seven mandibular teeth were evaluated according to the Demirjian's eight-grade dental maturity scale by one examiner. Dental age was compared to chronologic age (CA) using a paired t-test. Intra- and inter-observer agreements were assessed with 250 OPGs. Results The mean difference between DA and CA was statistically significant among genders (p = 0.004), and it was 0.50+/-1.90 years in girls and 0.77+/-1.86 years in boys. The mean DA was significantly higher (p<0.0001) than the mean CA in the entire studied group; therefore, dental development was considerably accelerated. The Intra- and Interclass Correlation Coefficient (ICC) for the assessment of DA were 0.964 and 0.961, respectively, which is Considered substantial agreement. Conclusion Results show that the Mean DAs of the studied group of Turkish children are significantly higher than the CAs. Overestimation is notable at the beginning of puberty.
Keywords: Demirjian's stages; Dental age; Dental maturation; MATURITY; ACCURACY; CURVES